Aflatoxin B1, zearalenone and deoxynivalenol in feed ingredients and complete feed from different Province in China. Issue 1 (December 2016) - Wu, Li; Li, Jianjun; Li, Yunhu; Li, Tiejun; He, Qinghua; Tang, Yulong; Liu, Hongnan; Su, Yongteng; Yin, Yulong; Liao, Peng
Abstract Background The current study was carried out to provide a reference for monitory of aflatoxin B1 (AFB1 ), zearalenone (ZEN) and deoxynivalenol (DON) contamination in feed ingredients and complete feeds were collected from different Province in China from 2013 to 2015. Methods A total of 443 feed ingredients, including 220 corn, 24 wheat, 24 domestic distillers dried grains with soluble (DDGS), 55 bran, 20 wheat shorts and red dog, 37 imported DDGS, 34 corn germ meal and 29 soybean meal as well as 127 complete feeds including 25 pig complete feed (powder), 90 pig complete feed (pellet), six duck complete feed and six cattle complete feed were randomly collected from different Province in China, respectively, by high-performance chromatography in combined with UV or fluorescence analysis. Results The incidence rates of AFB1, ZEN and DON contamination of feed ingredients and complete feeds were 80.8, 92.3 and 93.9 %, respectively. The percentage of positive samples for DON ranged from 66.7 to 100 %. Domestic DDGS and imported DDGS presented the most serious contamination AFB1, ZEN and DON contamination levels of feeds ranged from 61.5 to 100 %, indicated that serious contamination over the studied 3-year period. Conclusion The current data provide clear evidence that AFB1, ZEN and DON contamination of feed ingredients and complete feeds in different Province in China is serious and differs over past 3-year. The use of corn, domestic DDGS, imported DDGS and corn germ meal, which may be contaminated with these three mycotoxins, as animal feed may triggered a health risk for animal. Feeds are most contaminated with DON followed by ZEN and AFB1 . Mycotoxins contamination in feed ingredients and complete feeds should be monitored routinely in China.